KONTRIBUSI PAJAK TERHADAP PENDAPATAN ASLI DAERAH (Kajian Pada Pajak Hotel, Restoran, dan Hiburan di DKI Jakarta Periode 2010-2013) - Refianto Refianto; Michael Christian (Universitas Muhammadiyah Tangerang, 2018)
The target of local taxes supports the a better local development. DKI Jakarta as the capital city of Indonesia has its own strategic taxes sources. Some of them are hotel tax, restaurant tax, and entertainment tax. This aims to find out the taxes effectiveness and the taxes contribution of hotel tax, restaurant tax, and entertainment tax. Using the descriptive-quantitative, the period of the local real earning of DKI Jakarta is 2010-2013. The result explained that the hotel tax and restaurant tax in 2010-2013 were very effective. Meanwhile tha entertainment tax was slowing down to be ineffectve in 2013. The level of taxes contribution of hotel tax, restaurant tax, and entertainment tax are relatively small as it showed under 10% of each period. It is important to recalculate the number of hotels, restaurants, and types of enterntainment in DKI Jakarta. Using three types of local taxes and short period of local real earning, next researchers can use more types and longer period of local real earning.